Cell-type specific inhibitory plasticity in subicular pyramidal cells - Guinet, Alix; Grosser, Sabine; Özbay, Duru; Behr, Joachim; Vida, Imre (Frontiers in Cellular Neuroscience, 2024)
The balance between excitation and inhibition is essential to the proper function of cortical circuits. To maintain this balance during dynamic network activity, modulation of the strength of inhibitory synapses is a central requirement. In this study, we aimed to characterize perisomatic inhibition and its plasticity onto pyramidal cells (PCs) in the subiculum, the main output region of the hippocampus. We performed whole-cell patch-clamp recordings from the two main functional PC types, burst (BS) and regular spiking (RS) neurons in acute rat hippocampal slices and applied two different extracellular high-frequency stimulation paradigms: non-associative (presynaptic stimulation only) and associative stimulation (concurrent pre-and postsynaptic stimulation) to induce plasticity. Our results revealed cell type-specific differences in the expression of inhibitory plasticity depending on the induction paradigm: While associative stimulation caused robust inhibitory plasticity in both cell types, non-associative stimulation produced long-term potentiation in RS, but not in BS PCs. Analysis of paired-pulse ratio, variance of IPSPs, and postsynaptic Ca2+ buffering indicated a dominant postsynaptic calcium-dependent signaling and expression of inhibitory plasticity in both 2 PC types. This divergence in inhibitory plasticity complements a stronger inhibition and a higher intrinsic excitability in RS as compared to BS neurons, suggesting differential involvement of the two PC types during network activation and information processing in the subiculum.